Formante do cantor: revisão integrativa e desenvolvimento por meio de exercícios do trato vocal semiocluído - Matter, Suelen Scholl (2024)
Operatic singing, not amplified by microphones, implies requirements for the singer to be heard as a result of the accompaniment of the symphony orchestra. One of the ways to develop this skill is through specific articulatory adjustments that result in the singer's formant. Objective: to carry out an integrative review of the singer's formant and an analysis of the use of three different semi-occluded vocal tract exercises for its development. Method: the thesis is composed of two studies: the first, an integrative review focusing on the concepts, articulatory adjustments and perceptual-auditory dimensions underlying the singer's formant. The second study aimed to test exercises that could help the singer's formant production. The sample was composed of 18 opera singers, nine sopranos and nine tenors, without vocal alterations. Three different semi-occluded vocal tract techniques were analyzed (LaxVox, Styrofoam cup and High Resistance Straw). Vocal emissions were recorded before and immediately after each exercise and compared through auditory-perceptual analysis, acoustic parameters and proprioceptive self-report. Results: in study 1, it was identified that the concepts of the singer's formant were associated with vocal brightness and the acoustic correlate of greater high-frequency energy, with the grouping of the third and fourth formant. The way to obtain this sound is mainly related to lowering the larynx, widening the pharynx and bringing the tongue closer to the lower incisor teeth, generating an expansion of the entire vocal tract. This can be obtained by sopranos and tenors. In study 2, it was identified that the sopranos, who often already had the singer's formant, showed even more benefits after exercising the high-resistance straw, considered the most efficient among the three interventions. They showed gains in the phenomenon. The tenors in this research did not have a singer's formant, but they also benefited from presenting the phenomenon, with the LaxVox exercise being the most efficient. Final considerations: The singer's formant can be developed in sopranos and tenors with the help of the semi-occluded vocal tract exercises investigated in this research. They generate, in the acoustic sphere, an approximation of the third and fourth formants; in the perceptual scope, greater vocal projection, audibility, depth and/or vocal stability; and, in the proprioceptive scope, sensations of pharyngeal expansion and greater ease in projecting the voice